Detection of Toxoplasma gondii in swine sausages - De Oliveira Mendonça, André [UNESP]; Domingues, Paulo Francisco [UNESP]; Da Silva, Aristeu Vieira [UNESP]; Bergamaschi Pezerico, Sandia [UNESP]; Langoni, Hélio [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2004)
In order to evaluate the importance of swine sausages in toxoplasmosis epidemiology, Toxoplasma gondii presence was investigated in 70 samples of the product commercialized in the city of Botucatu-SP. Samples were analyzed by bioassay in mice and DNA amplification by Polymerase Chain Reaction (PCR). Although the parasite was not isolated from any sample in the bioassay, 33 (47.14%) samples were positive in the PCR. These results indicate that swine sausages probably have low importance as a source of infection for human toxoplasmosis in the studied region. Nevertheless, the great number of PCR positive samples shows that the protozoan may be present, but may be inactivated by salt added in sausage manufacture.
Keywords: Isolation; PCR; Swine sausage; Toxoplasma